Nearctomeris, a new genus of Pill Millipedes from North America, with a comparison of genetic distances of American Pill Millipede Genera (Glomerida, Glomeridae) - Wesener, Thomas (Zootaxa, 2012)
A new genus and species of the pill millipede order Glomerida, Nearctomeris inexpectata n. sp., n. gen., is describedfrom the Eastern United States. The description of Nearctomeris brings the total number of American Glomerida generato three. In two of three known localitites, Nearctomeris co-occurs with species of the genus Onomeris Cook, 1896.Onomeris and Nearctomeris have almost an identical size (4–5.5 mm) and dark colour, but can be readily distingusihedby numerous non-sexual and sexual characters. Sexual characters of the male telopod also place Nearctomeris into thefamily Glomeridae, while the third American pill millipede genus Glomeroides Chamberlin, 1922 belongs to theProtoglomeridae. A key to all American genera of Glomerida is presented. For the first time in the order Glomerida, thepartial cytochrome c oxidase I mitochondrial gene was analyzed for the three American genera of the Glomerida,Glomeroides, Onomeris, and Nearctomeris together with European genera currently placed in different families,Glomeridella and Trachysphaera, as outgroups. Distance, maximum parsimony and maximum likelihood methods wereemployed. Maximum parsimony and likelihood analyses did not lead to a well-resolved phylogeny, but found a weaklysupported sister-group relationship between Nearctomeris and Onomeris. All five analyzed pill millipede genera differgreatly in their uncorrected basepairs (15–22%), and moderately in their amino acids (5–10%). As in Onomeris, the closestrelative of Nearctomeris can probably be found among the Asian genera Hyleoglomeris Verhoeff, 1910 or Hyperglomeris Silvestri, 1917. In America, more attention should be given to the search for other small-bodied, cryptic, rare Glomerida.